基于有限元法的齿端修形设计及影响因素分析 - 刘晓勇; 杨忠林; 苏铁熊; 张翼 (Jixie chuandong)
Taking an increasing speed transmission gear pair as research objects,the longitudinal bending deformation and contact stress distribution of gear tooth meshing are analyzed with three dimension contact finite element analysis method.The results reasonability and credibility of the finite element method is verified through comparing the results of the classical method.For the tooth end bias load of contact stresses resulting from the elastic deformation of gear tooth,an approach for gear tooth end relief design and calculation is proposed according to tooth face deflection in the meshing process.The distribution of contact stresses is improved after gear tooth modification and the reasonability of the approach is validated.The influence law of normal force,tooth width of gear,pitch diameter and supporting span on the amount of gear tooth end relief is calculated and analyzed.The results show that all above factors have influence on gear tooth end relief and that the normal force and width-diameter ratio of gear has greater effects.